Influence of Planting Method and Nitrogen Dose on Growth and Yield of Quinoa (Chenopodium Quinoa Willd.) - Biswas, PK; Fatema, K; Rahman, A (Bangladesh Agronomy Journal, 2021)
The experiment was conducted at Sher-e-Bangla Agricultural University, Dhaka during Rabi season 2018-19 to find out the influence of planting methods and nitrogen dose on growth and yield of Quinoa-a highly nutritious super food newly introduced in Bangladesh. The experiment was laid out in a Split-plot design with 3 replications. Two planting methods viz., i) seed sowing (M1) and ii) seedling planting (M2) in the main plot and eight nitrogen doses viz., i) Control (F1), ii) 50 kg N ha-1 (F2), iii) 100 kg N ha-1 (F3), iv) 150 kg N ha-1 (F4), v) 180 kg N ha-1 (F5), vi) 200 kg N ha-1 (F6), vii) 220 kg N ha-1 (F7) and ix) 250 kg N ha-1 (F8) in the sub-plot were assigned. Almost all the studied characters were found statistically significant due to variation in treatments. The higher plant height, leaf number plant-1, branch number plant-1 and inflorescence height were observed in seedling transplantation than seeds sowing. Increment of nitrogen doses increased the plant height, leaves number plant-1, branch number plant-1, inflorescence height and SPAD value up to 150-200 kg N ha-1 and then decreased. Higher doses of nitrogenous fertilizer application increased the grain weight. Planting seedling with 150 kg N ha-1 showed the highest seed yield (1227.43 kg ha-1) which was similar to 180 kg N ha-. Cultivation of quinoa with 25 days old seedlings and 150 kg N ha-1 gave 206.77% higher yield compared to that of control and it was 64.71% higher in case of seeds sowing with similar nitrogen dose. Bangladesh Agron. J. 2021, 24(1): 83-92